Amoral familism in North Korean civil society - KIM, Isaac (KDI School, 2019)
The current state of North Korean studies is overly “securitized.” To better assess the multi-faceted problem that is North Korea today, greater attention in non-security areas is warranted. The objective of this paper is to diagnostically investigate the socio-psychological state of the North Korean people and recast the magnitude of the totalitarian realities. The research question is: Does Banfield’s (1958) “Amoral Familism” provide a useful framework for characterizing the kind of society that North Korea finds itself to have become today? This study uses simple statistics and a quantitative survey of 1,010 North Korean defectors. T-test results showed that most of the values were statistically significant and analysis of findings provides policy implications for both the defector community in South Korea as well as the future trajectory of the Korean peninsula.
Thesis(Master) --KDI School:Master of Development Policy,2019